2004
DOI: 10.1038/sj.bjc.6601682
|View full text |Cite
|
Sign up to set email alerts
|

Co-targeting IGF-1R and c-kit: synergistic inhibition of proliferation and induction of apoptosis in H 209 small cell lung cancer cells

Abstract: Most small cell lung cancers (SCLC) coexpress the c-kit protein tyrosine receptor kinase and its ligand stem cell factor, resulting in an autocrine loop. As SCLC growth is also driven by insulin-like growth factor-1 receptor (IGF-1R) signalling, tyrphostins AG 1024 and 1296 (inhibitors of IGF-1R and c-kit activity, respectively) were used to co-target these receptors in H 209 SCLC cells. Combination treatment caused synergy in proliferation inhibition and in apoptosis induction, and also enhanced reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 27 publications
0
30
0
4
Order By: Relevance
“…In fact, there is experimental evidence which suggests that trastuzimabresistant breast cancer is particularly sensitive to IMC-A12 (54). These observations, together with other examples, such as synergistic induction of apoptosis when small cell lung cancer is targeted by both c-KIT and IGF-IR inhibitors, suggest that IGF-IR blockade might enhance tumor sensitivity to other kinase inhibitors (66).…”
Section: Prospects For Combinations With Targeted Therapiesmentioning
confidence: 98%
“…In fact, there is experimental evidence which suggests that trastuzimabresistant breast cancer is particularly sensitive to IMC-A12 (54). These observations, together with other examples, such as synergistic induction of apoptosis when small cell lung cancer is targeted by both c-KIT and IGF-IR inhibitors, suggest that IGF-IR blockade might enhance tumor sensitivity to other kinase inhibitors (66).…”
Section: Prospects For Combinations With Targeted Therapiesmentioning
confidence: 98%
“…Consequently, novel therapies are urgently required and these will most likely arise from an improved understanding of the disease biology. There is now considerable evidence implicating multiple growth factors that act in an autocrine or paracrine fashion to drive SCLC proliferation (1)(2)(3)(4)(5). In particular, our laboratory has established the role of basic-fibroblast growth factor (FGF-2) in this disease (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…We have therefore used tissue arrays to analyze the protein expression of the six TKs which are believed to play the most significant roles in the progression of a number of human malignancies, and which are potential clinical targets for kinase inhibition (Blume-Jensen & Hunter 2001). We selected EGF-R, Her-2/neu, PDGF-R, insulinlike growth factor 1 receptor (IGF-1R), c-Abl and c-Kit for their pivotal involvement in a number of solid tumors and for the fact that each of these kinases can be targeted by newly developed, clinically available TKIs (George 2001, Scheijen & Griffin 2002, Janmaat & Giaccone 2003, Camirand & Pollak 2004. Furthermore, in each case, preclinical studies have already confirmed that these targets can be selectively neutralized by highly specific TKIs.…”
Section: Introductionmentioning
confidence: 99%